2015
DOI: 10.1111/hex.12388
|View full text |Cite
|
Sign up to set email alerts
|

People with insomnia: experiences with sedative hypnotics and risk perception

Abstract: Background Sedative hypnotics form an important part of managing insomnia and are recommended for short-term use. It is standard practice for clinicians to inform the patient to use medications only 'when required', but the use of these medications is often chronic. Little is known about the impact of standard labelling/instructions on promoting appropriate medication use for managing insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Of the seven components of the PSQI, use of sleep medication was the component with the highest score, and among those reporting fairly good or very good sleep quality, 63.6% (7 out of 11) took hypnotics three or more times a week. Unlike people with insomnia, who tend to take fewer sleep medications [ 34 ], in this study, people with schizophrenia who also had sleep issues had a higher level of acceptance of sleep medications, which is possibly due to their long history of taking antipsychotic medications. The qualitative data revealed that people with schizophrenia may accept a status quo of sleep quality as long as they are able to fall asleep even if it requires taking hypnotics.…”
Section: Discussionmentioning
confidence: 84%
“…Of the seven components of the PSQI, use of sleep medication was the component with the highest score, and among those reporting fairly good or very good sleep quality, 63.6% (7 out of 11) took hypnotics three or more times a week. Unlike people with insomnia, who tend to take fewer sleep medications [ 34 ], in this study, people with schizophrenia who also had sleep issues had a higher level of acceptance of sleep medications, which is possibly due to their long history of taking antipsychotic medications. The qualitative data revealed that people with schizophrenia may accept a status quo of sleep quality as long as they are able to fall asleep even if it requires taking hypnotics.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, it is commonly comorbid with medical and psychiatric disorders, increases risk for development of these disorders, and is associated with increased health care utilization and costs (Alexander et al, 2016; Anderson et al, 2014; Martin et al, 2017; Riemann, 2007; Taylor et al, 2007). Treatment of insomnia typically consists of prescription sedative-hypnotics and behaviorally based interventions (Cheung, Bartlett, Armour, Ellis, & Saini, 2016). Sedative-hypnotics, the most common treatment, are effective and reduce symptoms relative to placebos, but the evidence is not strong, especially long-term (Charles, Harrison, & Britt, 2009; Mitchell, Gehrman, Perlis, & Umscheid, 2012).…”
mentioning
confidence: 99%
“…Findings on medication‐taking and treatment decision‐making have been published in Health Expectations (Cheung et al . ) and Behavioral Sleep Medicine (Cheung et al . ), respectively.…”
Section: Methodsmentioning
confidence: 99%